PERILAKU NYENI ORANG JAWA SEBAGAI SALAH SATU KAJIAN FILSAFAT MANUSIA DALAM STUDI KASUS SENI PERTUNJUKAN - Priatmojo, Dhewangga; Tejo Bagus Sunaryo (Sanjiwani: Jurnal Filsafat, 2026)
Javanese nyeni behavior originates from the people's way of life, original form, and spirit, and is born out of the spontaneity of community life. During nyeni behavior, individuals may enter a trance-like state, wherein their consciousness is believed to be guided by sacred spirits. This research focuses on two main aspects: (1) How is the artistic behavior of Javanese society found in the traditional performing art of Kuda Lumping, and (2) what values are contained within it. Javanese nyeni behavior is found in the Kuda Lumping Turonggo Suro Lestari Budoyo art performance. Javanese nyeni behavior is found in the Kuda Lumping Turonggo Suro Lestari Budoyo art performance. The nyeni behavior of the Javanese people is manifested in the Kuda Lumping performance, particularly through the Turonggo Suro Lestari Budoyo art group. The expression of nyeni behavior in the Kuda Lumping Turonggo Suro Lestari Budoyo art performance is evident among the performing arts dancers, audience, and the society. The nyeni behaviors above have values that make performing arts dancers, the audience, and society have a sense of solidarity. Thus, this is a manifestation of harmony and balance in people's lives.